PENGARUH SENAM LOW IMPACT TERHADAP PENURUNAN KADAR GULA DARAH PADA LANSIA PENDERITA DIABETES MELITUS TIPE 2 - Djamanmona, Rolyn Frisca Djamanmona; Nurjanah, Fitri Nurjanah (Nursing Arts, 2023)
Diabetes Mellitus (DM) is a collection of metabolic diseases with hyperglycemia which can be caused by insulin deficiency, decreased insulin action, or both. Research purposes to determine the effect of low impact exercise on reducing blood sugar levels in the elderly with type 2 diabetes mellitus. Methods of research used in this study is quasi-experimental using a one group pretest posttest design. The sample in this study 15 respondents people with diabetes millitus who were selected with inclusion criteria. Primary and secondary data collection techniques. The results of the analysis using the paired t test there is a significant effect between low impact exercise on reducing blood sugar levels in the elderly with type 2 diabetes mellitus in the Work Area of the Inpatient Health Center Mariat District Sorong Regency with p value < (0.000 < 0.05). Conclusion of this research there is a significant effect between low impact exercise on reducing blood sugar levels in the elderly with type 2 diabetes mellitus in the Work Area of the Inpatient Health Center Mariat District Sorong Regency